Ecological Knowledge Management and Creative Economy Upgrading of Krajood Products in Phru Khuan Khreng, Thailand - Boonchat Mekkaeo; Anucha Thaisanong; Nattanicha Homgate; Nannapat Prompetch; Khemmathat Suwanmanee (PT. Global Research Collaboration, 2026)
This in-depth qualitative case study investigates the dynamics of ecological knowledge management and the creative upgrading of Krajood handicrafts in the Phru Khuan Khreng wetland, Nakhon Si Thammarat. The research aims to explore how indigenous wisdom adapts to contemporary economic pressures while maintaining its ecological integrity. Data were collected through in-depth interviews with five local sages, participant observations of two community enterprises, and focus group discussions with three interdisciplinary experts. The findings reveal three pivotal dynamics: (1) Upstream Ecological Wisdom, specifically the